EXPLORING GENDER DIFFERENCES IN DETERMINANTS OF BANK ALADIN SHARIA ADOPTION: A MULTI-GROUP ANALYSIS APPROACH - Lutfi, Bintang Aulia; Prasetyo, Ari; Timur, Yan Putra; Rifqi, Muhammad (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2023)
Introduction: This study aims to determine what factors lead people in East Java use Bank Aladin Sharia services based on gender differences. Methods: The PLS-SEM Multi Group Analysis approach is used as an evaluation model in this study's quantitative methodology, which makes use of SmartPLS 3.0. The information was gathered by having respondents living in East Java to fill out an online survey, which was then divided by gender. 417 respondents who met the requirements of being Indonesian citizens, Muslims, and capable cell phone users were used as the sample. Results: Performance expectations, social influence, and price values”generally have an impact on a customer's decision to adopt digital Islamic banking services. The same outcomes were also seen in the male data group, demonstrating again how customer intents to use Bank Aladin Sharia services were influenced by performance expectations, social influence, and price values. The pricing value variable is the only factor influencing customer intentions in this female data group. Conclusion and suggestion: The study results show that different factors encourage males and females to use Bank Aladin Sharia services. Researchers suggest that Islamic banks can increase public understanding of sharia digital banking services. This study has limitations on the UTAUT2 variable as an exogenous variable. In future research, it is possible to modify the UTAUT-2 model by including a moderating variable.